254 Bioavailability of Cu, Mn, and Zn from organic sources compared to sulfates. (7th December 2018) - Ball, J; Kegley, E; Beck, P; Powell, J
Abstract: Sixty crossbred beef calves (35 heifers and 25 steers; body weight = 254 ± 16.7 kg, ) were obtained from a single source. Liver biopsies were performed at least 25 days prior to study initiation and at the end of the study. Calves were weighed on day -1 and blocked by body weight and stratified within block by initial liver Cu concentration and assigned randomly to pen. Pens (n = 15; 4 calves/pen) within block (n = 5) were then assigned randomly to 1 of 3 dietary treatments: 1) Control– basal diet with no supplemental Cu, Mn, and Zn, 2) Sulfate– basal diet supplemented with Cu, Mn, and Zn from sulfate sources, or 3) Organic– basal diet supplemented with Cu, Mn, and Zn from organic sources (chelated with glycine). Supplemental levels were identical in supplemented diets and were 10 mg Cu, 20 mg Mn, and 20 mg Zn/kg of DM. The control diet analyzed 7 mg Cu, 18 mg Mn, and 35 mg Zn/kg. All diets contained 0.2% supplemental S as sodium sulfate. Body weights and blood for plasma extraction were collected on days 0, 27, 55, 83, 115, and 116. Dependent variables were analyzed using the MIXED procedure of SAS with pen as the experimental unit. Trace mineral supplementation or source did not affect ( P ≥ 0.55) body weights. Overall average daily gain from days 0 to 115 was greater in Sulfate and Control compared to Organic ( P = 0.02). A treatment × day interaction was detected for liver Cu concentrations as Organic and Sulfate increased from days 0 to 115 whereas Control decreased ( P < 0.01); however, Organic and Sulfate did not differ ( P = 0.18). Source and supplementation of Cu, Mn, and Zn for 116 days had a minimal impact in growing calves not previously deficient.